A roadmap for offering MOOC from an LMIC institution. Issue 4 (2nd October 2017) - Abidi, Syed Hani; Pasha, Aamna; Moran, Greg; Ali, Syed
ABSTRACT: MOOCs are massive open online courses that are globally accessible, free of charge. Given their cost-free and open accessibility, it is surprising that only a few institutions have offered MOOCs from low- and middle-income countries (LMICs). Pakistan recently made this short list of LMICs as the first two MOOCs were launched from the country, in 2014 and 2016. Drawing from that experience, the organizers of that course present a roadmap for LMIC institutions for developing a MOOC, focusing especially on the technological and pedagogical limitations that an LMIC institution might find deterring.